Restorative Management of Severe Localized Tooth Wear Using a Supraoccluding Appliance: A 5-Year Follow-Up - Tsz Leung Wong; Michael George Botelho (Case Reports in Dentistry)
This case report illustrates a novel conservative restorative management of a patient with bulimia nervosa who presented with severe localized upper palatal tooth wear and an anterior reverse overjet. This was achieved by using a localized bite raising or supraoccluding appliance, cemented on the lingual side of the lower anterior teeth to create interocclusal space, obviating the need for tooth reduction of the eroded upper palatal and incisal tooth surfaces. Surgical crown lengthening was performed to create a better aesthetic gingival architecture. All-ceramic restorations were provided on the upper anterior teeth to restore the tooth surface loss and provide a positive overbite and overjet. There was no complication or other observable biological change detected at the 5-year follow-up. The use of an appliance applying the supraoccluding technique, or Dahl concept, is a safe, conservative, and useful treatment option in the management of localized tooth wear.